Validity of LKPD Cognitive Conflict Strategy to Reduce Misconceptions in Hydrocarbon Material: Validitas LKPD Strategi Konflik Kognitif untuk Mereduksi Miskonsepsi pada Materi Hidroakrbon - Dwi Irmayanti; Bertha Yonata (PendIPA Journal of Science Education, 2025)
The development of the cognitive conflict-based Student Worksheet (LKPD) plays a role in reducing students' misconceptions regarding hydrocarbons. In this study, the LKPD was created in print format to facilitate the completion of exercises. This LKPD contains information presentations, true statements, and ambiguous statements to create cognitive conflicts for students, as well as reflection questions for conceptual reconstruction. The aim of this research is to determine the validity of the cognitive conflict strategy LKPD. This study employs a Research and Development (R&D) approach based on the 4D development model, which includes Definition, Design, Development, and Dissemination. However, it only reaches the development stage. The research utilized a validation sheet instrument for the LKPD. The validation results indicate that the developed LKPD received a median score ranging from 4 to 5, indicating that the LKPD is valid based on content validity and construct validity. The conclusion of this study states that the developed cognitive conflict strategy LKPD is valid and can serve as an effective learning medium to reduce students' misconceptions about hydrocarbons based on validity aspects.